Eco-friendly cationic modification of cotton fabrics for improving utilization of reactive dyes. Issue 57 (25th June 2015) - Fang, Long; Zhang, Xiaodong; Ma, Jinhai; Sun, Deshuai; Zhang, Botao; Luan, Jimei
<x xml:space="preserve">Abstract</x> The cotton fabric was modified by the eco-friendly cationic polymer. The modified cotton fabric could be dyed with reactive dyes without salt. This investigation provided a feasible and eco-friendly way to realize salt-free dyeing of reactive dyes.